STEROID-UNMASKED CENTRAL DIABETES INSIPIDUS IN A PATIENT WITH PITUITARY METASTASIS FROM BREAST CARCINOMA: A CASE REPORT - Woon, Yip Xiong; Chua, Yi Jiang; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Pituitary metastases are rare but clinically significant, most commonly originating from breast or lung cancers. Diabetes insipidus (DI) is the most frequent manifestation of posterior pituitary involvement. We describe a case of pituitary metastasis presenting with panhypopituitarism and central diabetes insipidus (CDI), initially unmasked by adrenal insufficiency. CASE A 68-year-old female with metastatic left breast carcinoma, post-mastectomy and on hormonal therapy, presented with a generalized tonic-clonic seizure and a Glasgow Coma Scale (GCS) score of 4. She exhibited persistent hypoglycemia requiring repeated dextrose corrections, along with hypotensive episodes. Brain CT revealed a well-defined iso-to-hyperdense lesion in the sellar and suprasellar regions (2.0 × 2.5 × 3.0 cm). Subsequent pituitary MRI showed a heterogeneously enhancing lobulated mass (2.2 × 2.5 × 3.0 cm) with loss of normal anterior pituitary architecture. Laboratory tests confirmed adrenal and thyroid insufficiency, with a random cortisol level of 284 nmol/L, TSH at 0.072 µIU/mL, and free T4 below 3.20 mmol/L. Hydrocortisone therapy was initiated, leading to a significant increase in serum sodium from 132 to 160 mmol/L. Serum and urine osmolality measured 318 and 183 mOsm/kg, respectively, with urine sodium under 10 mmol/L, raising suspicion for CDI. Desmopressin was commenced, resulting in improved sodium (145 mmol/L) and osmolality levels (serum 335 mOsm/kg, urine 646 mOsm/kg). Gonadotropin levels (FSH, LH) and estradiol were also low, indicating panhypopituitarism. A multidisciplinary team confirmed pituitary metastasis secondary to breast carcinoma. The patient was transitioned to palliative care with hormone replacement: hydrocortisone, desmopressin, and levothyroxine. CONCLUSION Hypocortisolism in breast cancer patients should raise suspicion for pituitary metastasis. Polyuria after steroid therapy may indicate underlying central diabetes insipidus. Prompt diagnosis and hormone replacement can significantly enhance symptom management and patient well-being.